Socio-demographic and Clinical Profile of Children with Asthma attending Chest Clinic at B. P. Koirala Institute of Health Sciences, Nepal - Yadav, Satish (Birat Journal of Health Sciences, 2021)
Introduction: Asthma in children is one of the most common chronic diseases and little information available on factors associated with this disease in our part of the world. Objective: The present study is an attempt to find out the socio-demographic and clinical profile of children with asthma. Methodology: This was a retrospective analysis of data of asthmatic children below 14 years attending pediatric chest clinic from July 2014 till March 2016. Results: Of the 200 children, there were 142 (71%) males. The median age of presentation was 3 years and 139 (69.5%) from the age group 1-5years One third had poorly controlled asthma. Comorbidity was present in 59(29.5%) and allergic rhinitis (7%) was the most common. 90.5% had onset of wheezing before 5 years of age. Family history of asthma and/or atopy and smoking was present in 24% and 31%, respectively. 22% had exposure to pet animals. Upper respiratory tract infection (URTI) (37%) was the most common trigger for exacerbation. Cough (99%) and fast breathing (98%) were the most common symptoms. Conclusion: The majorities were males of young age with rhinitis as most common co-morbidity and many of them had a history of parental smoking at home. One third of them had poorly controlled asthma which shows the need for proper management of asthma including its comorbidity in younger children and changing certain habits like parental smoking at home.